Latest incidence and electrocardiographic predictors of atrial fibrillation: a prospective study from China. Issue 3 (5th February 2023) - Wei, Yong; Zhou, Genqing; Wu, Xiaoyu; Lu, Xiaofeng; Wang, Xingjie; Wang, Bin; Wang, Caihong; Shen, Yahong; Peng, Shi; Ding, Yu; Xu, Juan; Cai, Lidong; et al.
Abstract: Background: China bears the biggest atrial fibrillation (AF) burden in the world. However, little is known about the incidence and predictors of AF. This study aimed to investigate the current incidence of AF and its electrocardiographic (ECG) predictors in general community individuals aged over 60 years in China. Methods: This was a prospective cohort study, recruiting subjects who were aged over 60 years and underwent annual health checkups from April to July 2015 in four community health centers in Songjiang District, Shanghai, China. The subjects were then followed up from 2015 to 2019 annually. Data on sociodemographic characteristics, medical history, and the resting 12-lead ECG were collected. Kaplan–Meier curve was used for showing the trends in AF incidence and calculating the predictors of AF. Associations of ECG abnormalities and AF incidence were examined using Cox proportional hazard models. Results: This study recruited 18, 738 subjects, and 351 (1.87%) developed AF. The overall incidence rate of AF was 5.2/1000 person-years during an observation period of 67, 704 person-years. Multivariable Cox regression analysis indicated age (hazard ratio [HR], 1.07; 95% confidence interval [CI]: 1.06–1.09; P < 0.001), male (HR, 1.30; 95% CI: 1.05–1.62; P = 0.018), a history of hypertension (HR, 1.55; 95% CI: 1.23–1.95; P < 0.001), a history of cardiac diseases (HR, 3.23; 95% CI: 2.34–4.45; P < 0.001), atrial premature complex (APC) (HR, 2.82; 95% CI: 2.17–3.68; P < 0.001), atrial flutter (HR, 18.68; 95% CI: 7.37–47.31; P < 0.001), junctional premature complex (JPC) (HR, 3.57; 95% CI: 1.59–8.02; P = 0.002), junctional rhythm (HR, 18.24; 95% CI: 5.83–57.07; P < 0.001), ventricular premature complex (VPC) (HR, 1.76; 95% CI: 1.13–2.75, P = 0.012), short PR interval (HR, 5.49; 95% CI: 1.36–22.19; P = 0.017), right atrial enlargement (HR, 6.22; 95% CI: 1.54–25.14; P = 0.010), and pacing rhythm (HR, 3.99; 95% CI: 1.57–10.14; P = 0.004) were independently associated with the incidence of AF. Conclusions: The present incidence of AF was 5.2/1000 person-years in the studied population aged over 60 years in China. Among various ECG abnormalities, only APC, atrial flutter, JPC, junctional rhythm, short PR interval, VPC, right atrial enlargement, and pacing rhythm were independently associated with AF incidence.